Randomized Trial of Benznidazole for Chronic Chagas' Cardiomyopathy - Morillo, C. A. (2015)
BACKGROUND:The role of trypanocidal therapy in patients with established Chagas´ cardiomyopathy is unproven.METHODS:We conducted a prospective, multicenter, randomized study involving 2854 patients with Chagas´ cardiomyopathy who received benznidazole or placebo for up to 80 days and were followed for a mean of 5.4 years. The primary outcome in the time-to-event analysis was the first event of any of the components of the composite outcome of death, resuscitated cardiac arrest, sustained ventricular tachycardia, insertion of a pacemaker or implantable cardioverter-defibrillator, cardiac transplantation, new heart failure, stroke, or other thromboembolic event.RESULTS:The primary outcome occurred in 394 patients (27.5%) in the benznidazole group and in 414 (29.1%) in the placebo group (hazard ratio, 0.93; 95% confidence interval [CI], 0.81 to 1.07; P=0.31). At baseline, a polymerase-chain-reaction (PCR) assay was performed on blood samples obtained from 1896 patients; 60.5% had positive results for Trypanosoma cruzi on PCR. The rates of conversion to negative PCR results (PCR conversion) were 66.2% in the benznidazole group and 33.5% in the placebo group at the end of treatment, 55.4% and 35.3%, respectively, at 2 years, and 46.7% and 33.1%, respectively, at 5 years or more (P<0.001 for all comparisons). The effect of treatment on PCR conversion varied according to geographic region: in Brazil, the odds ratio for PCR conversion was 3.03 (95% CI, 2.12 to 4.34) at 2 years and 1.87 (95% CI, 1.33 to 2.63) at 5 or more years; in Colombia and El Salvador, the odds ratio was 1.33 (95% CI, 0.90 to 1.98) at 2 years and 0.96 (95% CI, 0.63 to 1.45) at 5 or more years; and in Argentina and Bolivia, the odds ratio was 2.63 (95% CI, 1.89 to 3.66) at 2 years and 2.79 (95% CI, 1.99 to 3.92) at 5 or more years (P<0.001 for interaction). However, the rates of PCR conversion did not correspond to effects on clinical outcome (P=0.16 for interaction).CONCLUSIONS:Trypanocidal therapy with benznidazole in patients with established Chagas´ cardiomyopathy significantly reduced serum parasite detection but did not significantly reduce cardiac clinical deterioration through 5 years of follow-up. (Funded by the Population Health Research Institute and others; ClinicalTrials.gov number, NCT00123916; Current Controlled Trials number, ISRCTN13967269.).